Corruption: Challenge to Internationalization - Altbach, Philip (International Higher Education, 2012)
Corruption is a growing problem for higher education worldwide. It is especially a challenge for internationalization since monitoring and controlling cross-border corruption is quite difficult. Among the aspects of corruption are the involvement of dishonest agents and recruiters, false credentials, fake examination results, and others.